Metformin Induces Apoptosis in Human Pancreatic Cancer (PC) Cells Accompanied by Changes in the Levels of Histone Acetyltransferases (Particularly, p300/CBP-Associated Factor (PCAF) Protein Levels) - Izabela Szymczak-Pajor; Józef Drzewoski; Ewa Świderska; Justyna Strycharz; Anna Gabryanczyk; Jacek Kasznicki; Marta Bogdańska; Agnieszka Śliwińska (MDPI AG, 2023)
Accumulating evidence (mainly from experimental research) suggests that metformin possesses anticancer properties through the induction of apoptosis and inhibition of the growth and proliferation of cancer cells. However, its effect on the enzymes responsible for histone acetylation status, which plays a key role in carcinogenesis, remains unclear. Therefore, the aim of our study was to evaluate the impact of metformin on histone acetyltransferases (HATs) (i.e., p300/CBP-associated factor (PCAF), p300, and CBP) and on histone deacetylases (HDACs) (i.e., SIRT-1 in human pancreatic cancer (PC) cell lines, 1.2B4, and PANC-1). The cells were exposed to metformin, an HAT inhibitor (HATi), or a combination of an HATi with metformin for 24, 48, or 72 h. Cell viability was determined using an MTT assay, and the percentage of early apoptotic cells was determined with an Annexin V-Cy3 Apoptosis Detection Assay Kit. Caspase-9 activity was also assessed. SIRT-1, PCAF, p300, and CBP expression were determined at the mRNA and protein levels using RT-PCR and Western blotting methods, respectively. Our results reveal an increase in caspase-9 in response to the metformin, indicating that it induced the apoptotic death of both 1.2B4 and PANC-1 cells. The number of cells in early apoptosis and the activity of caspase-9 decreased when treated with an HATi alone or a combination of an HATi with metformin, as compared to metformin alone. Moreover, metformin, an HATi, and a combination of an HATi with metformin also modified the mRNA expression of SIRT-1, PCAF, CBP, and p300. However, metformin did not change the expression of the studied genes in 1.2B4 cells. The results of the Western blot analysis showed that metformin diminished the protein expression of PCAF in both the 1.2B4 and PANC-1 cells. Hence, it appears possible that PCAF may be involved in the metformin-mediated apoptosis of PC cells.